The Relationship Between Knowledge and Attitudes Towards Adolescent Reproductive Health Behavior in Public High Schools of Makassar City - Asyima Asyima (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Adolescence is a transitional period vulnerable to reproductive health problems. Lack of knowledge and inappropriate attitudes can affect adolescent reproductive health behavior. This study aims to analyze the relationship between knowledge and attitudes towards adolescent reproductive health behavior in Public High Schools of Makassar City. This study used a cross-sectional design with a quantitative approach. The study population was grade X and XI students of Public High Schools in Makassar City with a total sample of 384 respondents selected using proportional stratified random sampling technique. Data were collected using validated structured questionnaires. Data analysis used chi-square test and multiple logistic regression with 95% confidence level. Of 384 respondents, 58.6% had poor knowledge, 61.2% had negative attitudes, and 64.8% had poor reproductive health behavior. Chi-square test results showed a significant relationship between knowledge and reproductive health behavior (p=0.001; OR=2.45; 95%CI:1.67-3.59) and attitudes with reproductive health behavior (p=0.000; OR=3.12; 95%CI:2.08-4.68). Multivariate analysis showed that attitude was the most dominant factor affecting adolescent reproductive health behavior (p=0.000; OR=2.89; 95%CI:1.85-4.52). There is a significant relationship between knowledge and attitudes towards adolescent reproductive health behavior. Attitude is the dominant factor affecting reproductive health behavior. Comprehensive reproductive health education programs are needed to improve knowledge and change adolescent attitudes.